Design of a Footflash Application as a Footwork Detector for Badminton Players - Christine, Jessica (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
As a national sport in Indonesia, badminton requires agile footwork to achieve success in competitions. However, players often struggle to maintain consistent techniques and receive real-time feedback. A qualitative approach using the design thinking method was applied, including interviews, usability testing, and prototype observation. In the define stage, How Might We questions were formulated to guide the solution. The ideate and prototype stages resulted in key features such as motion detection and progress tracking. In the test stage, four active badminton players evaluated the usability and effectiveness of the application. The usability test results showed that color-coded motion tracking on the Apple Watch helped users understand their mistakes. Feedback from users prompted design iterations on performance analysis features, video tutorials, and training intensity adjustments. This study demonstrates that directly listening to users’ opinions and experiences is essential in designing sports technology that is effective and easy to use. Future development will focus on incorporating artificial intelligence (AI) to tailor training based on user abilities and progress, as well as gamification elements to enhance user engagement.